2002
DOI: 10.1053/jlts.2002.34380
|View full text |Cite
|
Sign up to set email alerts
|

Reduced use of intensive care after liver transplantation: Patient attributes that determine early transfer to surgical wards

Abstract: Part 1 of our report, presented in the same issue of the Journal, shows that immediate postoperative extubation and direct transfer to the surgical ward is safe and reduces reliance on the intensive care unit in most liver transplant recipients. However, there is no method to preoperatively predict which patients will need ventilatory support after surgery. To address this issue, we examined the relationship between perioperative patient attributes and extubation outcome in patients entered into our immediate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
3

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 33 publications
0
27
0
3
Order By: Relevance
“…This also applies for Child C patients and recipients with acute hepatic failure or retransplantation (mostly due to INF) [26], who in our analysis could only be extubated on the intensive care unit. Mandell et al reported by means of a multivariate logistical regression analysis of 147 patients, that encephalopathy and body mass index (>35) were criteria for failure of primary extubation in the operating theatre [27]. O'Meara et al reported on similar findings in pediatric transplantations [24], and Biancofiore et al reported of a multivariate logistical regression analysis of 168 patients who received primary extubation within the first three postoperative hours [14].…”
Section: Discussionmentioning
confidence: 49%
“…This also applies for Child C patients and recipients with acute hepatic failure or retransplantation (mostly due to INF) [26], who in our analysis could only be extubated on the intensive care unit. Mandell et al reported by means of a multivariate logistical regression analysis of 147 patients, that encephalopathy and body mass index (>35) were criteria for failure of primary extubation in the operating theatre [27]. O'Meara et al reported on similar findings in pediatric transplantations [24], and Biancofiore et al reported of a multivariate logistical regression analysis of 168 patients who received primary extubation within the first three postoperative hours [14].…”
Section: Discussionmentioning
confidence: 49%
“…IPE may allow the patient to avoid ICU admission, reducing hospital length of stay and ICU-associated costs. 20,[23][24][25] However, safe avoidance of the ICU after LT requires careful redirection of nursing resources and very close collaboration among the anesthesiology, ICU, and ward teams. Indeed, others contend that a period of postoperative ventilation allows graft function to be consolidated with less sympathetic activation and protects the recipient from the risks of atelectasis, aspiration, or reintubation for surgical reexploration if required.…”
Section: System-based Considerations For Postoperative Management Resmentioning
confidence: 99%
“…After liver transplantation, patients can be extubated in the operating room (11)(12)(13)(14). On the other hand, close monitoring and laboratory tests have to be continued in the ICU.…”
Section: Anesthetic Management Of Abdominal Organ Transplantationmentioning
confidence: 99%